Development of an aptamer-based diagnostic method targeting PRRSV-induced cytopathic effects - In-Hwan Oh; Phat-Loc Nguyen; Dae-Young Park; Jin-Pyo Lee; Woo-Ri Shin; Su-Min Lee; Jiho Min; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2026)

Integrating RT-RPA/CRISPR system for the end-point visual detection of Mayaro virus - Christine Ardelle Marquez; Gna Ahn; Woo-Ri Shin; Eung Je Lee; Chan-Hee Lee; Hye-Kwon Kim; Yang-Hoon Kim; Ji-Young Ahn (Molecular & Cellular Toxicology, 2026)

Unveiling the toxicological impact of yeast vacuoles in Daphnia - Taehwan Kim; Hyo Jin Choi; Woo-Ri Shin; Uyen Le Ngoc Phuong; Dae-Young Park; Ji-Young Ahn; Yang Hoon Kim; Jiho Min (Molecular & Cellular Toxicology, 2025)

Toxicological implications of storage conditions on yeast vacuole properties and activities - Hyo Jin Choi; Taehwan Kim; Woo-Ri Shin; Jin-Pyo Lee; Uyen Le Ngoc Phuong; Ji-Young Ahn; Yang-Hoon Kim; Jiho Min (Molecular & Cellular Toxicology, 2024)

Atelocollagen Scaffold Enhances Cartilage Regeneration in Osteochondral Defects: A Study in Rabbits - Ji-Chul Yoo; Man Soo Kim; Sueen Sohn; Sang Hun Woo; Yu Ri Choi; Andrew S. Kwak; Dong Shin Lee (Tissue Engineering and Regenerative Medicine, 2024)

Synergistic outcomes of Chlorella-bacterial cellulose based hydrogel as an ethylene scavenger - SeonHyung Lee; Gna Ahn; Woo-Ri Shin; Jae-Won Choi; Yang-Hoon Kim; Ji-Young Ahn (Carbohydrate Polymers, 2023)

In silico molecular docking validation of procalcitonin-binding aptamer and sepsis diagnosis - Dae-Young Park; Woo-Ri Shin; Sang Yong Kim; Quang-Thai Nguyen; Jin-Pyo Lee; Do-Young Kim; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2023)
Background Procalcitonin (PCT) is a protein that can be used as a biomarker for sepsis detection. Sepsis is a disease where early diagnosis is crucial. Using PCT for sepsis diagnosis can be a new alternative that overcomes limitations of traditional sepsis diagnostic methods. Objective To develop a sepsis diagnostic platform for PCT detection using a novel material called aptamer. Results Aptamers that could specifically bind to PCT were selected and various molecular biology analysis methods were utilized to confirm the binding affinity between selected aptamers and PCT. Additionally, in silico structural analysis was conducted to gain a more detailed understanding of the binding structure between the aptamer and PCT using the results of molecular experiments as supporting evidence. Ultimately, an aptamer-based PCT detection platform was developed and its ability to detect PCT in general and serum samples with high sensitivity and specificity was confirmed. Conclusion Through this study, we were able to develop a technique for early disease diagnosis using aptamer-based protein detection. We also performed aptamer binding validation studies using a combination of molecular validation and in silico validation methods.

Recent advances in engineering aptamer-based sensing and recovery of heavy metals and rare earth elements for environmental sustainability - Woo-Ri Shin; Gna Ahn; Jin-Pyo Lee; In-Hwan Oh; Ji-Young Ahn; Yang-Hoon Kim; Soryong Chae (Chemical Engineering Journal, 2023)

3D structural analysis of aptamer and diagnostic platforms for detecting hepatocellular carcinoma - Woo-Ri Shin; Dae-Young Park; Hyun-Ju Um; Gna Ahn; Sang Yong Kim; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2023)

Correction: Cardiac biomarkers and detection methods for myocardial infarction - Sang Young Kim; Jin-Pyo Lee; Woo-Ri Shin; In-Hwan Oh; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2023)

The present and future of minimally invasive methods for Alzheimer's disease diagnosis - In-Hwan Oh; Woo-Ri Shin; JinHee Ahn; Jin-Pyo Lee; Jiho Min; Ji-Young Ahn; Yang-Hoon Kim (Toxicology and Environmental Health Sciences, 2022)

Cardiac biomarkers and detection methods for myocardial infarction - Sang Young Kim; Jin-Pyo Lee; Woo-Ri Shin; In-Hwan Oh; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2022)

Modifications of mRNA vaccine structural elements for improving mRNA stability and translation efficiency - Sun Chang Kim; Simranjeet Singh Sekhon; Woo-Ri Shin; Gna Ahn; Byung-Kwan Cho; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2022)

Structure-based molecular docking approach for identifying S‑formylglutathione hydrolase from Sphingobium chungbukense - Jin-Pyo Lee; Woo-Ri Shin; Gna Ahn; Hyun-Ju Um; Young-Chang Kim; Sang Yong Kim; Ji-Young Ahn; Yang-Hoon Kim (Toxicology and Environmental Health Sciences, 2021)

Codon optimization of the synthetic 3-ketosphinganine reductase (3KSR) protein for enhancing sphingolipid biosynthetic enzyme expression - Hyun-Ju Um; Woo-Ri Shin; Simranjeet Singh Sekhon; Sung Min Woo; Young-Chang Kim; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2021)

Heterologous expression of a novel serine palmitoyltransferase from Sphingobium chungbukense - Hyun-Ju Um; Woo-Ri Shin; Simranjeet Singh Sekhon; Sung Min Woo; Young-Chang Kim; Ji-Young Ahn; Yang-Hoon Kim (Toxicology and Environmental Health Sciences, 2021)

Aptamer-linked immobilized sorbent assay for detecting GMO marker, phosphinothricin acetyltransferase (PAT) - Woo-Ri Shin; Mun-Jong Lee; Simranjeet Singh Sekhon; Ji Hun Kim; Sun Chang Kim; Byung-Kwan Cho; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2020)

Production of 8S- and 10S-hydroxy polyunsaturated fatty acids by recombinant Escherichia coli cells expressing mouse arachidonate 8S-lipoxygenase - Kyung-Chul Shin; Woo-Ri Kang; Min-Ju Seo; Dae Wook Kim; Deok-Kun Oh (Biotechnology Letters, 2019)

Production of δ-decalactone from linoleic acid via 13-hydroxy-9(Z)-octadecenoic acid intermediate by one-pot reaction using linoleate 13-hydratase and whole Yarrowia lipolytica cells - Woo-Ri Kang; Min-Ju Seo; Jung-Ung An; Kyung-Chul Shin; Deok-Kun Oh (Biotechnology Letters, 2016)

Decision supporting frame to estimate chronic exposure suspicion to VOC chemicals using mixed statistical model - Byeong-Chul Kang; Yu-Ri An; Yeon-Kyung Kang; Ga-Hee Shin; Seung-Jun Kim; Seong-Yong Hwang; Suk-Woo Nam; Jae-Chun Ryu; Jun-Hyung Park (Molecular & Cellular Toxicology, 2013)

Ornithinibacillus scapharcae sp. nov., isolated from a dead ark clam - Na-Ri Shin; Tae Woong Whon; Min-Soo Kim; Seong Woon Roh; Mi-Ja Jung; Young-Ok Kim; Jin-Woo Bae (Antonie van Leeuwenhoek, 2012)

H89, an inhibitor of PKA and MSK, inhibits cyclic-AMP response element binding protein-mediated MAPK phosphatase-1 induction by lipopolysaccharide - Il Je Cho; Na Ri Woo; In Chul Shin; Sang Geon Kim (Inflammation Research, 2009)

Environmental estrogenic effects and gonadal development in wild goldfish (Carassius auratus) - Chun-Ri Li; Sang-Hoon Lee; So-Sun Kim; Andre Kim; Keun Woo Lee; Ming Lu; Hee-Eun Kim; Im-Jung Kwak; Yun-Ju Lee; Dong-Kyoo Kim; Jung-Sick Lee; Shin-Won Kang; et al. (Environmental Monitoring and Assessment, 2009)